O processo produtivo na mineração de areia no Rio Poti em Teresina-Piauí : um olhar para a saúde, o trabalho e o ambiente - Palha, Mirian Perpétua e Silva (2006)
This descriptive and cross-sectional survey was designed to evaluate the workers’ health, including occupational risks factors, and the environmental damages caused by sand mining, using hydraulical dredges, on the banks and the riverbed of the Poti river, in Teresina, in Northeast Brazil. Twenty-one dredges were visited, and 18 owners or managers and 75 workers were interviewed. Their main roles were divers, provided manual labors, engine operators, machine operators and administrators. The study showed that the potential risks for workers’ health, included physical, ergonomics, chemical, biological and accidental risks. The most important diseases related to the tasks were respiratory infections, back pain, dermatosis, and clinical manifestations related to barotraumas; the latter occurring only in those who worked as divers performing standard diving. Reports of fatal accidents with divers, and swimmers drowning who had not succeeded in leaving deep holes in the riverbed were also discovered. Serious environmental damages caused by this economical activity were demonstrated, mainly deforestation of the marginal vegetation on the riversides, contamination of the river water with petroleum derivatives, and the development of deep holes in the riverbed. Besides this, the exhaustion of the sand reserves (after an average period of four years of dredging in each explored area) demanded constant movement of dredges along the Poti riverbed, contributing to the gradual deterioration of the environment in the surrounding neighborhoods. In spite of the existence of an environmental legislation, and the action of regulating agencies, little has been done for an appropriate re-vegetation program of the degraded areas. In general, the main actions of the dredges owners, aimed at the recovery of the degraded environment, had been: to keep the minimum distance of the sand box at least 100 meters from the river banks, obeying the environmental preservation zones, and the construction of narrow channels for water draining back into the river. These measures, even so prospicious, are still far from accomplishing the restoration of environmental damages caused by sand dredging of the Poti River.